2008
DOI: 10.1007/s10551-008-9752-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Satisfaction with a Client’s Management During a Prior Audit Engagement, Trust, and Moral Reasoning on Auditors’ Perceived Risk of Management Fraud

Abstract: auditor trust, fraud risk, moral reasoning, professional skepticism,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 43 publications
1
36
0
2
Order By: Relevance
“…Previous studies have also shown that auditors are less likely to detect the signs of fraud when they have had positive experiences with the client and/or when they believe that the management is honest. Specifically, Kerler and Killough (2009) find that auditors who have previous positive experiences with clients will trust them more, and thus they become less skeptical in their fraud risk assessment compared to those whose previous experience with the client was a negative one. In a similar vein, a study by Popova (2012) shows that previous experience with clients (she refers it to as client-specific experiences) is influential in determining the initial expectations of the risks of a material misstatement.…”
Section: Situational Skepticism and Initial Fraud/error Expectationmentioning
confidence: 93%
“…Previous studies have also shown that auditors are less likely to detect the signs of fraud when they have had positive experiences with the client and/or when they believe that the management is honest. Specifically, Kerler and Killough (2009) find that auditors who have previous positive experiences with clients will trust them more, and thus they become less skeptical in their fraud risk assessment compared to those whose previous experience with the client was a negative one. In a similar vein, a study by Popova (2012) shows that previous experience with clients (she refers it to as client-specific experiences) is influential in determining the initial expectations of the risks of a material misstatement.…”
Section: Situational Skepticism and Initial Fraud/error Expectationmentioning
confidence: 93%
“…Pincus (1990) and Bernardi (1994) found that auditors' prior beliefs about the existence of fraud were a significant factor in the detection of fraud. Finally, Kerler and Killough (2009) found that the level of an auditors' trust in the client increased (decreased) as an auditor became more (less) satisfied with the actions of the client. As the level of trust decreased for the auditors who were less satisfied with their clients, the level of the auditors' fraud-risk assessments increased.…”
Section: Trust and Auditors' Judgmentsmentioning
confidence: 97%
“…Where ongoing interaction with key management personnel leads to identification with their goals and objectives, situational trust is elevated and, as a consequence, professional scepticism is negatively impacted. Kerler and Killough () find that an auditor's satisfaction with the client is positively associated with the trust they express towards that client. Importantly, this increased trust led to fraud risk assessments that were less sceptical.…”
Section: Insights For Professional Scepticism In Auditingmentioning
confidence: 99%